ON LOCAL TWO-POINT PROBLEM FOR THE EQUATION WITH THE OPERATOR OF GENERALIZED DIFFERENTIATION - Negrych, M. P.; Symotyuk, M. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
A local two-point problem with the oprator of Gelfond-Leontiev generalized differentiation with a complex argument is investigated. The conditions of unity and existence of the solution of the problem are obtained. It is proved that such conditions are satisfied for almost all (relative to Lebesgue measure) node of interpolation.